Reimagining Leadership in Islamic Education: Transforming Madrasah Aliyah through Innovation - Suratman; Sri Susmiyati; Nurhamid (Managere: Indonesian Journal of Educational Management, 2025)
The research originates from the issue of students' low academic performance, a shortage of educators, limited infrastructure, financial constraints, low motivation, and performance gaps, which lead to unequal learning outcomes and challenges in lesson planning. This study investigates the role of innovative leadership in enhancing educational quality, focusing on the strategies implemented by madrasah principals to improve teaching outcomes, school management, and student performance. The research employs a mixed-method approach using a sequential explanatory design. The population and sample consist of teachers and principals of Madrasah Aliyah in Indonesia. Data collection was conducted using questionnaires and interviews. Quantitative data were analyzed with the assistance of Lisrel software, while qualitative data were examined using the Miles and Huberman method. The findings indicate a positive and significant influence of innovative leadership on the quality of education. Integrating quantitative results from SEM analysis with qualitative insights from interviews provides a comprehensive understanding of how leadership influences education quality, highlighting that the creativity of madrasah principals in leadership contributes significantly to improving graduate quality, educator quality, the learning process, school management, and overall educational outcomes. This study's implications show that applying innovative leadership that integrates quantitative and qualitative data can improve the quality of education overall.